Pengaruh penggunaan metode eksperimen ditinjau terhadap hasil belajar IPA dari kemampuan komunikasi - Ening Sry Hastuti; Hidayati Hidayati (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2018)
This study aims to determine the difference between science study results using experimental methods and methods talks in terms of communication skill. The type of research is quasi experiment. Data collection technique using documentation, questionnaire, and test. Data analysis technique using descriptive analysis and anacova. Descriptively, science study results using experimental method in very high level while methods talks in high level. Communication skill of experimental methods in very high level and methods talks in high level. Comparatively, there’s an effect of experimental methods on science study results in terms of communication skill